Evolution of the inherited cardiac condition transition service: establishing the need for a dedicated service. (2nd February 2022) - Cowley, Bethan; Mackay, Rachel
Abstract : In this month's BANCC's feature, Bethan Cowley, a lead nurse for inherited cardiac conditions and Rachel Mackay, a clinical nurse specialist, reflect on the importance of a dedicated and bespoke service for people with inherited cardiac conditions.